Investigating magmatic processes in the early Solar System using the Cl isotopic systematics of eucrites. (1st December 2019) - Barrett, T.J.; Barnes, J.J.; Anand, M.; Franchi, I.A.; Greenwood, R.C.; Charlier, B.L.A.; Zhao, X.; Moynier, F.; Grady, M.M.
Abstract: Generally, terrestrial rocks, martian and chondritic meteorites exhibit a relatively narrow range in bulk and apatite Cl isotope compositions, with δ 37 Cl (per mil deviation from standard mean ocean chloride) values between −5.6 and +3.8‰. Lunar rocks, however, have more variable bulk and apatite δ 37 Cl values, ranging from ∼−4 to +40‰. As the Howardite-Eucrite-Diogenite (HED) meteorites represent the largest suite of crustal and sub-crustal rocks available from a differentiated basaltic asteroid (4 Vesta), studying them for their volatiles may provide insights into planetary differentiation processes during the earliest Solar System history. Here the abundance and isotopic composition of Cl in apatite were determined for seven eucrites representing a broad range of textural and petrological characteristics. Apatite Cl abundances range from ∼25 to 4900 ppm and the δ 37 Cl values range from −3.98 to +39.2‰. Samples with lower apatite H2 O contents were typically also enriched in 37 Cl but no systematic correlation between δ 37 Cl and δD values was observed across samples. Modelled Rayleigh fractionation and a strong positive correlation between bulk δ 66 Zn and apatite δ 37 Cl support the hypothesis that Cl degassed as metal chlorides from eucritic magmas, in a hydrogen-poor environment. In the case of lunar samples, it has been noted that δ 37 Cl values of apatite positively correlate with bulk La/Yb ratio. Interestingly, most eucrites show a negative correlation with bulk La/Yb ratio. Recently, isotopically light Cl values have been suggested to record the primary solar nebular signature. If this is the case then 4 Vesta, which accreted rapidly and early in Solar System history, could also record this primary nebular signature corresponding to the lightest Cl values measured here. The significant variation in Cl isotope composition observed within the eucrites are likely related to degassing of metal chlorides.